The many deaths of Mary Dobie: murder, politics and revenge in nineteenth-century New Zealand - Hastings, David (Auckland University Press, 2015)
"'Dreadful murder at Opunake', said the Taranaki Herald, 'Shocking outrage', the Evening Post in Wellington when they learned in November 1880 that a young woman called Mary Dobie had been found lying under a flax bush near Ōpunake on the Taranaki coast with her throat cut so deep her head was almost severed. In the midst of tensions between Māori and Pākehā, the murder ignited questions: Pākehā feared it was an act of political terrorism in response to the state's determination to take the land of the tribes in the region. Māori thought it would be the cue for the state to use force against them, especially the pacifist settlement at Parihaka. Was it rape or robbery, was the killer Māori or Pākehā? In this book, David Hastings takes us back to that lonely road on the Taranaki coast in nineteenth-century New Zealand to unravels the many deaths of Mary Dobie - the murder, the social tensions in Taranaki, the hunt for the killer and the lessons that Māori and Pākehā learnt about the murder and about themselves."--Publisher information